Extent of paranasal sinus involvement and its prognostic value in nasopharyngeal carcinoma: Proposed modification in the current UICC/AJCC staging system. (July 2021) - Wang, Xiao-Yi; Zhu, Si-Yu; WU, Wei-Jie; Li, Hao-Jiang; Li, Jiao; Lin, Xiao-Feng; Li, Li; Liu, Li-Zhi
Highlights: Paranasal sinus involvement (PSI) is an independent prognostic factor for NPC. The appropriate position in TNM staging system and diagnostic criteria of PSI has not reach on a uniform consensus yet. NPC patients with PSI should be classified into two groups: PSI-slight (sinus bone wall erosion only) and PSI-severe (tumor penetrate into sinus cavity). That survival outcomes of the patients with PSI-severe in T3 category are similar to those in AJCC T4 category disease. NPC patients with PSI-severe is recommended to classify as T4 category in AJCC staging system for NPC. Abstract: Purpose: This study aimed to evaluate the prognostic value of paranasal sinus involvement (PSI) in NPC and to explore its appropriate position in the current AJCC staging system. Materials and methods: Pretreatment MRI of 1317 patients with NPC treated with intensity-modulated radiotherapy (IMRT) between January 2010, and January 2013, were reviewed retrospectively. Survival was compared between patients with PSI-slight (sinus bone wall erosion only) and PSI-severe (tumor penetrated into sinus cavity). Multivariable analysis was performed to identify the independent predictors of survival. Results: The study included 1317 patients (median age 46 years; range, 11–78 years). PSI-slight was present in 15.2% (200/1317) patients and PSI-severe in 20.0% (263/1317) patients. Overall survival (OS), distant metastasis–free survival (DMFS), loco-regional recurrence–free survival (LRFS), and progression-free survival (PFS) were significantly lower in patients with PSI-severe (all P < .05). In multivariable analysis, PSI-severe was an independent prognostic factor for OS, DMFS, LRFS, and PFS (all P < .05). 96 AJCC T3 category patients with PSI-severe were reclassified as T4 category. The revised T category had significantly better predictive value (higher C-index) than that the AJCC system for survival (OS, .661 vs. .652; DMFS, .655 vs. .650; P < .05 for all). Conclusion: PSI-severe is an independent negative prognostic factor in nasopharyngeal carcinoma, which is recommended to be classified as T4 category in the 8th AJCC staging system for NPC.